Pengembangan Model Pembelajaran Shooting Sepakbola Melalui Permainan Menembakkan Bola ke Gawang Pada Siswa SDI Al-Kautsar Teluk Kodek - Nulhadi, Agus; Herlina, Herlina; Burhan, Zakir; Ashari, L. Hasan (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to produce a shooting learning model in football games to improve shooting accuracy learning outcomes in football games through developing learning models. This research is research and development or better known as R&D. The development method that the author uses is the Borg & Gall development model which has been varied, namely (1) conducting initial model research, (2) creating a new model in the form of a shooting learning model in football games, (3) validating football learning experts and learning experts ( physical education teacher), (4) conducting small-scale trials with 10 students, (5) product revision by football learning experts and learning experts (PJOK teachers), (6) conducting large-scale trials with 30 students, (7) product revisions based on trials large group. The data analysis technique uses quantitative data in the form of scores converted into percentages. The results of the research show that the soccer shooting learning model for training shooting accuracy in learning the game of soccer for junior high school students is very good/usable. These results were obtained from validation by football learning experts who showed a percentage of (model I) 90.6% (model II) 86.6% and physical education teacher learning experts (model I) 93.3% (model II) 90.6%. The assessment from small-scale trials obtained a percentage of 94.3%. And the assessment from large-scale trials obtained a percentage of 95.6%.